Legends and Legacies of Siti Jenar: Ecstatic Sufism and the Politics of Shath - Woodward, Mark; Gohier-Mangkubumi, Lea Ontosinah (UIN Sunan Kalijaga Yogyakarta, 2024)
The legend of Siti Jenar is among the most widely known and controversial tales in Javanese Islamic literature. While the details vary enormously, the core of the story is the same. Siti Jenar is the saint (wali) who passes beyond religion, as it is usually defined. He comes to know that there is ultimately only one reality – that of Allah – and that we all share in it. He is put on trial for publicly proclaiming the doctrine of the unity of being (wahdat al-wujud) that identifies the human soul with the essence of Allah (dat) and for rejecting modes of ritual performance required by Shari’ah including the Friday prayer. He was then executed on orders from the other wali. There are many versions of the story in Javanese chronicles (babad) and religious texts. Many more that circulate as oral tradition. There is a continuous string of new books, most of the in Indonesian instead of Javanese and websites retelling the story for contemporary audiences.